2010
DOI: 10.1016/j.virusres.2010.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Porcine reproductive and respiratory syndrome virus (PRRSV) could be sensed by professional beta interferon-producing system and had mechanisms to inhibit this action in MARC-145 cells

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) causes an economically important disease in swine-producing area, and interferon beta (IFN-beta) is the first responder against the animal virus infection. However, whether PRRSV could induce the production of IFN-beta is controversial. In this paper, we first time found that PRRSV could phosphorylate IFN-regulatory factor 3 (IRF-3) and weakly activate the IFN-beta promoter in MARC-145 cells in early infection, but the activations of IRF-3 and IFN-bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 36 publications
3
28
0
Order By: Relevance
“…Our previous study found that PRRSV could weakly trigger the activation of IRF-3 as well as induce the activation of IFN-␤ promoter at 24 h p.i., but their activities were rapidly inhibited in following infection. That is, PRRSV could be sensed by professional beta interferon-producing system in MARC-145 cells and had mechanisms to inhibit this action in MARC-145 cells (Shi et al, 2010). So our present work supplied another evidence that the endoribonuclease of PRRSV nsp11 could antagonize the induction of IFN-␤.…”
Section: His-144 and Lys-173 Were Essential For Nsp11 As An Interferosupporting
confidence: 55%
See 3 more Smart Citations
“…Our previous study found that PRRSV could weakly trigger the activation of IRF-3 as well as induce the activation of IFN-␤ promoter at 24 h p.i., but their activities were rapidly inhibited in following infection. That is, PRRSV could be sensed by professional beta interferon-producing system in MARC-145 cells and had mechanisms to inhibit this action in MARC-145 cells (Shi et al, 2010). So our present work supplied another evidence that the endoribonuclease of PRRSV nsp11 could antagonize the induction of IFN-␤.…”
Section: His-144 and Lys-173 Were Essential For Nsp11 As An Interferosupporting
confidence: 55%
“…Our previous study and others have found that nsp1, nsp2 and nsp11 from PRRSV were the IFN antagonists (Beura et al, 2010;Shi et al, 2010). Sun et al (2010) found that ubiquitindeconjugating activity of nsp2 antagonized the type I interferon.…”
Section: His-144 and Lys-173 Were Essential For Nsp11 As An Interferomentioning
confidence: 86%
See 2 more Smart Citations
“…P orcine reproductive and respiratory syndrome (PRRS) is an emergent catastrophic swine disease characterized by serious reproductive failure in pregnant sows and severe respiratory distress in piglets and growing pigs (Suradhat and Thanawongnuwech, 2003;Diaz et al, 2005;Shi et al, 2010). The culprit in PRRS is a positivestranded RNA virus of the order Nidovirales and family Arteriviridae called PRRS virus (PRRSV) (Ropp et al, 2004), which delays neutralizing antibody response and causes viremia and persistent infection leading to PRRS (Plagemann, 2004).…”
Section: Introductionmentioning
confidence: 99%